MARGINALISATION IN THE DANISH LABOUR MARKET - Laužadytė, Agnė (Ekonomika, 2011)
In this paper, I estimate different time hazard models of the exit from different labour market states – unemployment, employment and inactivity – in Denmark. I find that women and individuals over fifty are more likely to experience long-term unemployment and inactivity. The less educated and unskilled workers are found to be another risk group to face marginalisation. Being previously employed reduces the risk of inactivity and increases the probability of re-entry to employment, while long-term unemployment or inactivity makes workers more likely to return to these labour market states in the future. Living in biggest Danish cities where job competition is high is a disadvantage, but it has a positive effect on labour market performance of persons over fifty. And finally, I find that those who have stayed in job for one year tend to remain employed, while persons inactive for longer than one year face a much higher risk of marginalisation.